Enhancing Entrepreneurial Mindsets Through STEM Education - Kaya-Capocci, Sila.; Peters-Burton, Erin. (Cham : Springer International Publishing : Imprint: Springer, 2023)
Entrepreneurship is defined in different fields with definitions ranging from a specific perspective such as starting a business to a broader perspective such as a process of establishing new social, economic, environmental, institutional, cultural and/or scientific environments. There has been some movement toward entrepreneurship in STEM education through hackathons and makerspaces, but they tend to be limited to informal settings. In higher education, there seems to be a border line between business schools and education departments. This book aims to remove the borders between the Business Schools and the Department of Education and help Business Schools to develop their educational practices further and help Education Departments to develop their knowledge of entrepreneurship from its formal discipline. The purpose of this book is to bring together experts from STEM education and the formal discipline of entrepreneurship to explore the role of STEM in everyday life through an entrepreneurial lens and show how this integration can broaden STEM education practices.
PART 1: Entrepreneurial Mind of STEM Education in Theory -- Chapter 1. The Link between Entrepreneurship and STEM Education -- Chapter 2. Strengthening Bridges between STEM Education and Entrepreneurship: Pathways to societal empowerment towards sustainability -- Chapter 3. Cultivating Entrepreneurial Leadership Skills through STEM Education -- Chapter 4. Innovative Pedagogy and Practice for E-STEM Learning -- Chapter 5. An Entrepreneurial STEM Teaching Framework: Integrating business and STEM education -- PART 2: Example Practices for Fostering an Entrepreneurial STEM Mindset -- Chapter 6. Increasing the Pro-entrepreneurial Attitude of Students through Interdisciplinary Action in STEM Related Fields -- Chapter 7. From Think Tank to Shark Tank: Engineer to entrepreneur -- Chapter 8. Educating for STEM: Developing entrepreneurial thinking in STEM (EntreSTEM) -- Chapter 9. Fostering an Entrepreneurial Mindset through Project-based Learning and Digital Technologies in STEM Teacher Education -- Chapter 10. Back to School: An examination of teachers' knowledge and understanding of entrepreneurship education -- Chapter 11. Integrated and Innovative STEM Education: The Development of a STEM Education Minor -- PART 3: Empirical Results of Enhancing an Entrepreneurial STEM Mindset -- Chapter 12. Fostering Integrated STEM and Entrepreneurial Mindsets through Design Thinking -- Chapter 13. Inspiring the Next Generation of Innovators Through a Multidisciplinary Entrepreneurship and STEM Educational Outreach Programme -- Chapter 14. Pitching STEM: A Communicative Approach to Entrepreneurship in STEM Classrooms -- PART 4: The Ways of Conducting an Assessment of Entrepreneurial STEM Education -- Chapter 15. Bioengineering as a Vehicle to Increase the Entrepreneurial Mindset -- Chapter 16. Theatre-based Creativity Activities for the Development of Entrepreneurial Mindsets in Engineering -- Chapter 17. The Use of Digital Formative Assessment for Integrated Entrepreneurial STEM Education. .
Keywords: Education; Entrepreneurship; New business enterprises; Education -- Research; Education, Higher; Education Science; Entrepreneurship; Educational Research; Higher Education